Case Study on Chikungunya in an Infant - Vindhiya, K.; Selvendran, C. (New Horizons in Medicine and Medical Research Vol. 12, 2022)
The present case report highlights the effect of chikungunya in an infant. Chikungunya is an arboviral disease caused by the chikungunya virus, which belongs to the Togaviridae family and belongs to the genus Alpha virus. Aedes aegypti and Aedes albopictus mosquitos carry the disease. The main causes of epidemics are virus genetic adaptation and mosquito adaptation to the cold temperature, both of which lead to enhanced infectivity and spread. Chikungunya is a self-limiting disease with complete recovery being the rule. Risk of mortality is increased by indiscriminate use of corticosteroids, nonsteroidal antiinflammatory drugs (NSAIDS) especially aspirin, which can contribute to thrombocytopenia, gastrointestinal bleeding, nausea, vomiting and gastritis.